EVALUATING CLOUD MIGRATION SECURITY RISKS: DEVELOPMENT AND VALIDATION OF AN ENTERPRISE-LEVEL ASSESSMENT FRAMEWORK - Arun Harikrishnan (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article presents a comprehensive risk assessment framework for organizations transitioning from traditional data centers to cloud environments, addressing the critical security challenges inherent in cloud migration. Through a mixed-method approach combining systematic literature review, expert interviews (n=45), and multiple case studies across diverse industries, we develop and validate a structured framework for evaluating and mitigating security risks in cloud migration initiatives. The framework encompasses four key dimensions: data security, technical infrastructure, operational continuity, and regulatory compliance. The findings reveal that 73% of cloud migration security incidents stem from inadequate pre-migration risk assessment, while organizations utilizing structured risk assessment frameworks demonstrate a 62% reduction in security incidents during migration. The proposed framework introduces a novel scoring mechanism for risk prioritization and provides actionable mitigation strategies aligned with major compliance requirements (GDPR, HIPAA, PCI DSS). Validation across twelve enterprise-scale migrations demonstrates the framework's effectiveness in identifying critical security gaps and reducing risk exposure by an average of 47%. This article contributes to both theory and practice by providing a systematic approach to security risk assessment in cloud migration, while offering practical guidelines for security professionals and IT managers engaged in cloud transformation initiatives.